PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ERA MULIA ABADI SEJAHTERA - Asti Setya Hardhiyanti; Pompong Budi Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
An effective leadership style application of work discipline in managing human resources in a company will affect the work behavior of employees which will ultimately affect the overall performance of the company. The purpose of this study was to determine the effect of leadership style on employee performance and the effect of work discipline on employee performance at PT Era Mulia Abadi Sejahtera in the city of Malang. The instrument of this research used a questionnaire. Samples were taken as many as 30 employees of PT Era Mulia Abadi Sejahtera respondents in the city of Malang. Analysis and data processing using SPSS. The results of this study indicate that leadership style has no effect on employee performance, while work discipline has an effect on employee performance.